CIGALAZADE YUSUF SINAN PASHA (C. 1545-1606) - (:unkn) unknown (MEDITERRANEA, 2015)
Scipione Cigala, alias Cigalazade Yusuf Sinan (c. 1545-1605), a Christian convert to Islam, was one of the most important high-level administrators of the Ottoman ruling elite. His name is still widely recognized in Cagaloglu, one of the most popular tourist districts of Istanbul. He held the position of the kaptan-i derya (chief admiral) and sadrazam (grand-vizier) during the late 16th and early 17th centuries, a complex period for the Ottoman ruling elite. In this period, the balance of power was unstable and it was nearly impossible to hold a position for more than a few years; in some circumstances, no more than a few months. The dynasty wanted to protect itself against the strengthened vizier households by shortening the tenure of their administrators. This was their solution to prevent high-level administrators from establishing new networks. In such a period of turmoil, Yusuf Sinan Pasha always found a way to stay in high levels of the administration by accommodating himself to the changing conditions; and he managed this even though Safiye Sultan, one of the most powerful women in the Ottoman Court, was hostile towards him. Under these circumstances, he held his position as a kaptan-i derya between 1591-1595 and 1599-1604 and, during that time, he was one of the most powerful commanders in the Mediterranean; he regularly plundered Venetian coasts and galleys. His Christian origins have always been a matter of dispute. In this study, I will shed light on his life and career on the basis of new documents from the Venetian State Archives read in conjunction with the Ottoman chronicles.
Keywords: Kaptan-i derya; Venice; Cigalazade; Grand-Vizier; Ottoman ruling elite